(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This paper delves into the intriguing concept of making visible things invisible, reminiscent of the magical cloak from the Harry Potter series. Dispelling the notion of actual magic, it reveals the science and art behind achieving this effect through graphics tricks. The proposed solution introduces the creation of a 'Color Picker' utilizing Image Processing techniques. By exploring methods to manipulate objects based on color or texture, this study presents a step-by-step approach devoid of Python and OpenCV. The process involves capturing and storing the backdrop frame, identifying specific colors, generating masks, and ultimately producing the illusion of invisibility. This abstract encapsulates the essence of the paper, promising insights into crafting a magical experience through technology.